1986
DOI: 10.1002/eji.1830161111
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptides and β‐chain gene rearrangements reveal a diversified T cell repertoire for a λ light chain third hypervariable region

Abstract: Twelve L3T4+ Ly-2.2- subclones, derived from 4 independent BALB/c T cell lines, responded to a combination of the I-Ed molecule and a synthetic peptide corresponding to residues 91-108 of the lambda light chain from BALB/c myeloma protein M315 (alpha, lambda 2). Peptide analogues in which the mutated residues Arg95 or Asn96 were exchanged with the corresponding germ-line-encoded Ser95 or Thr96 had an abolished or greatly reduced capacity to stimulate T cell clones. However, responses of subclones to an analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 25 publications
6
50
1
Order By: Relevance
“…In the 1980s it became clear that immunoglobulins are processed and presented by antigen-presenting cells (APC) and that V-region-derived Id-peptides are displayed on MHC class II molecules to Id-specific CD4 + T cells [5][6][7][8]. It was further demonstrated that B cells continuously processed their own BCR and constitutively presented Id-peptides on their MHC class II molecules [9][10][11] [12].…”
Section: Id-specific T Cells Recognize V-region Sequence Determinantsmentioning
confidence: 99%
“…In the 1980s it became clear that immunoglobulins are processed and presented by antigen-presenting cells (APC) and that V-region-derived Id-peptides are displayed on MHC class II molecules to Id-specific CD4 + T cells [5][6][7][8]. It was further demonstrated that B cells continuously processed their own BCR and constitutively presented Id-peptides on their MHC class II molecules [9][10][11] [12].…”
Section: Id-specific T Cells Recognize V-region Sequence Determinantsmentioning
confidence: 99%
“…To test this directly we have used recently established T-cell clones specific for an idiotope of A2315 in the context of the I-Ed MHC antigen (7,8). These clones, like the T cells studied in vivo before (4, 5), recognize an idiotypic determinant on A2315 around amino acid positions 94, 95, and 96 (7, 8 …”
Section: Introductionmentioning
confidence: 99%
“…This proposal was based on the findings that T cells specific for an idiotype on the A2 light chain from MOPC315 cells (A2315) recognized denatured forms of A2315 (4) and that this recognition was under H-2-linked immune response (Ir) gene control (5). The hypothesis has been supported and extended by later work (6)(7)(8). Similar ideas have recently been proposed by others (9,10), and MHC-restricted T cells specific for idiotypes (11,12) and allotypes (13) have been described.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Probes 11M1, 11M2, and 13F1 were isolated from cosmid clone TA 28 .1 (34). Probe IOFI is a 3.0-kb Barn HI fragment isolated from the genomic (EMBL) clone 4B2A1-a-2 (35) . Ja region probes 4,5,7,8,10, and 16(Cb) were kindly provided by Drs.…”
mentioning
confidence: 99%